Effect of autonomic nervous system resection extent on urinary dysfunction in robotic rectal cancer surgery - Sodai Arai; Hiroyasu Kagawa; Akio Shiomi; Yusuke Yamaoka; Shoichi Manabe; Chikara Maeda; Yusuke Tanaka; Shunsuke Kasai; Akifumi Notsu; Yusuke Kinugasa (Annals of Gastroenterological Surgery)
Abstract Aim We investigated whether autonomic nervous system resection during robotic rectal surgery contributes to urinary dysfunction and to what extent. Methods This retrospective cohort study included patients who underwent rectal surgery for primary rectal cancer between December 2011 and April 2021. We identified urinary dysfunction risk factors and examined the effect of autonomic nervous system resection extent on urinary dysfunction occurrence, with urinary dysfunction defined as a residual urine volume of >50 mL. Urinary dysfunction with no improvement over 1 y was defined as permanent urinary dysfunction. Results Of 1017 eligible patients, 78 (7.7%) required autonomic nervous system resection. Lateral lymph node dissection was performed in 357 patients (35.1%). Urinary dysfunction was observed in 102 patients (10.0%). We studied 32 (41.0%) of 78 patients who underwent autonomic nervous system resection and 82 (23.0%) of 357 patients who underwent lateral lymph node dissection presented with urinary dysfunction. Multivariate analysis revealed that lateral lymph node dissection and autonomic nervous system resection were significant predictors of urinary dysfunction. The urinary dysfunction incidence was notably higher in patients with autonomic nervous system unilateral total resection of at least one side than in those with bilateral preservation (65.4% vs. 28.8%, p < 0.01), and permanent urinary dysfunction exclusively occurred in these patients. Conclusion In robotic surgery, autonomic nervous system resection and lateral lymph node dissection were independent risk factors for urinary dysfunction. Furthermore, the extent of autonomic nervous system resection may increase the risk of permanent urinary dysfunction.